Effects of temperature and storage period on polarization of poly(vinylidene fluoride-trifluoroethylene) ultrathin films - SHI Zhi (Journal of Materials Engineering, 2021)
The polarization switching properties of P(VDF-TrFE) ultrathin films with different storage periods were measured. The dependence of polarization properties on temperature and storage period was investigated. The experimental results suggest that the relative remanent polarization (Pr/Pr0) remains on a relatively high level of 0.70 at 60℃, 106 polarzation swiching test, even to the ultrathin film capacitors stored in atmosphere for five months. The time stability model of polarization switching is predicted by the evolution of polarization switching with the number of electric field cycles. Moreover, when the changes of the molecular chain are simulated by different storage periods and testing temperatures, an inhibited hydrogen fluoride (HF) gas formation scheme in the capacitors was proposed. This work further validated the time stability model and microscopic dynamics associated with trapped charge. These results provide an effective method for designing an optimum protocol for flexible electronic devices based on P(VDF-TrFE) copolymer ultrathin films.